The relationship between early life stress and working memory in adulthood: A systematic review and meta-analysis. Issue 6 (3rd July 2019) - Goodman, Jade B.; Freeman, Emily E.; Chalmers, Kerry A.
ABSTRACT: Exposure to early life stress has been linked to impairment in cognitive functioning in adulthood. The aim of this study was to systematically review the literature on the relationship between early life stress and working memory, a central component of cognitive functioning. Database searches yielded 358 abstracts matching the search terms. Abstract screening followed by full-text review resulted in 26 publications suitable for inclusion, of which 23 were included in the meta-analysis. Results of the meta-analysis suggested exposure to early life stress was associated with poorer working memory. Even though there were a wide variety of working memory tasks used, this effect was significant for both phonological and visuospatial working memory tasks, and both visual and aural task presentation modalities. The effect was also found in samples with and without clinical psychopathology. This review provides recommendations for future research and implications for clinical practice.